A computer program as an object of copyright: problems of legal protection - Філик, Наталія Володимирівна; Омельченко, Ганна Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article investigates the legal nature of a computer programme, problems of legal protection of computer programmes as copyright object have been revealed, and the ways to solve the mentioned problems have been suggested. The authors analyze peculiarities of legal protection of computer programmes according to rules of copyright law and possibilities to protect separate elements of compute programmes by norms of patent law. Separately the authors investigate the question of formation and development of IT industry in Ukraine. Attention has been paid to problems that hinder the mentioned development and ways to remove them.